Çocuklarda paranazal sinüs enfeksiyonlarının değerlendirilmesi - (:unkn) unknown (My University, 2006)
Akut bakteriyel sinüzitin tanısı, uzayan viral üst solunum yolu enfeksiyonu belirtilerine (>10-14 gün) ya da sinüziti gösteren belirgin klinik bulgulara dayanır. Çocuklarda sinüzit tanısı klinik bulgularla konur. Viral ÜSYE sinüzit ile benzer radyolojik bulgulara neden olur, bu nedenle sinüslerin düz grafileri dikkatli yorumlanmalıdır. Radyolojik değerlendirme yineleyen sinüziti olan, sinüzit tanısı kuşkulu bulunan ya da komplikasyon geliştiğinden kuşkulanılan olgularda istenmelidir. Ülkemizde penisiline orta düzeyde dirençli S. .pneumoniae oranı yaklaşık %20-25, yüksek dirençli S. pneumoniae oranı ise yaklaşık %3'tür. H. influenzae da beta laktamaz pozitiflik oranı yaklaşık %8'dir. Tedavide amoksisilin önerilen ilk tercihtir. Ancak yuvaya giden, yaşı <2 yıl olan ya da son üç ay içinde antibiyotik tedavisi alan olgularda amoksisilin yüksek doz (80-90 mg/kg/gün) verilmelidir. İlk 3gün içinde tedaviye yanıtın görülmediği olgularda sırasıyla 2. ve 3. basamak antibiyotikler kullanılmalıdır. Tedavide mukolitik ajanların, antihistaminiklerin, dekonjestanların bir yararı kanıtlanamamıştır, yalnızca %0.9 NaCI burun damlaları önerilir.

Diagnosis of acute bacterial sinusitis in children depends on obvious clinical signs showing sinusitis or unexpectedly longer duration of any upper respiratory tract infection symptoms (>10-14 days). In children, sinusitis is a clinical diagnosis. Viral upper respiratory tract infections can lead to the same appearance of sinusitis on X-ray of paranasal sinuses. So, the physician should be carefully evaluating the X-rays. X-rays should be done in any case with recurrent sinusitis or any sinusitis with complicatons related to infection. The frequency of pneumococci with moderate penicillin-resistance is 20-25 % and high-level penicillin resistance is 3% in Turkey. Among H influenzae strains in Turkey, beta-lactamase producing strains cover about 8%. Amoxycillin is the first choice antibiotic in treatment. But, if the case age is under two- years, or is attending a kindergarten, or if there is a positive history for antibiotic usage in the last three months, amoxycillin should be used in high doses (80-90 mg/kg/d) in the management of these cases with high risk for resistant pneumococci. At the end of the first three days of treatment, if the case is not recovering, antibiotic modality should be changed into second or third level of choices. There is no data on clinical benefit of mucolytic syrups, antihistaminics, or decongestants. The only other treatment known to be beneficial is NaCl 0.9% nasal saline drops.
Management of paranasal sinusitis in children
Keywords: Kulak, Burun, Boğaz